The neurotrophic factor receptor RET regulates IL‐10 production by in vitro polarised T helper 2 cells. Issue 12 (18th October 2014) - Almeida, Afonso R. M.; Fonseca‐Pereira, Diogo; Arroz‐Madeira, Sílvia; Ribeiro, Hélder; Labão‐Almeida, Carlos; Veiga‐Fernandes, Henrique
Abstract : T helper (Th) cells are critical players in the modulation of immune response outcomes. Activation of Th cells gives rise to various subsets of effector cells that are controlled via specialised regulatory T cells or through self‐regulation via production of IL‐10. However, the environmental factors that regulate IL‐10 production by Th cells remain poorly understood. Here, we show that the neurotrophic factor receptor rearranged during transfection (RET) downregulates IL‐10 production by Th cells from C57BL/6 mice. We found that effector Th cells express RET and that RET's neurotrophic factor partners are mainly produced by LN stromal cells, allowing context‐dependent Th‐cell regulation. Despite being dispensable for Th‐cell homeostasis, RET controls IL‐10 production in Th2 cells: RET‐deficient Th cells exhibited increased IL‐10 production, while triggering of Th1/2 cells with neurotrophic factors, namely glial‐derived neurotrophic factor and neurturin, decreased the expression of IL‐10. In agreement, the important IL‐10 transcription factor Maf was upregulated in RET‐deficient Th2 cells and down‐regulated upon RET signalling activation by glial‐derived neurotrophic factor family ligands. Thus, our study uncovers neurotrophic factors as novel regulators of Th‐cell function, revealing that Th cells and neurons can be regulated by similar signals in tissue‐specific responses.